DINAMIKA MEDITASI DALAM ISLAM - Rojaya Rojaya; Dody S Truna (Studia Sosia Religia, 2026)
According to Joachim Wach, religious experience has three forms of expression: thought, action, and fellowship. These experiences, both personal and collective, are dynamic in the sense that they can change, influenced by both psychological and sociological conditions. This research uses a document study method. The existing documents were studied through document content analysis. The results show that meditation in Islam, as a form of religious experience, has undergone changes. This is evident in prayer, seclusion, dhikr, and tilawah.